Malaysia Seaport Development towards Embracing Industrial Revolution 4.0: Enhancing the Quality and Competitiveness of Seaport Industry - et.al, Mohamad Rosni Othman (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Seaport industry is a dynamic industry which is experiencing a rapid growth. Industrial Revolution 4.0 merges the digital, physical and biological system to enhance the capabilities of the industry. It creates a platform which enables the seaport industry to build its effectiveness, reliability and governance towards improving the quality of seaport services. Accordingly, the evolution of seaport services entails the application of technologies so that the industry can fulfil its customer satisfaction goals. In line with this notion, the purpose of this research is to examine the relationship between Industrial Revolution 4.0 and the quality of seaport services. This research employed the quantitative content analysis, covering seaport effectiveness, seaport reliability and seaport governance. The respondents of this research comprised expert individuals within the seaport industry cluster. The results revealed that there is a significant correlation between the adaption of IR 4.0 and seaport quality. This research offers a truly novel policy innovation towards achieving seaport competitiveness.